"The useless mouths", and other literary writings - Beauvoir, Simone de, 1908-1986 (Beauvoir, Simone de, 1908-1986. Works. 2004., 2011)
This title brings to English-language readers literary writings - several previously unknown - by Simone de Beauvoir. Highlights of the volume include a new translation of the 1945 play 'The Useless Mouths, ' the unpublished 1965 short novel 'Misunderstanding in Moscow', and more.